(untitled) (Journal of Medical Sciences, 2024)
Aims: oral squamous cell carcinoma (OSCC) is the most common form of oral cancer and is currently largely treated by surgery and/or radiation. Significant complications can occur because of these treatments. Adjunct therapies that are safer and less toxic are being explored. This study aims to investigate the potential anti-cancerous effect of the flaxseed on oral squamous carcinoma cells in vitro and determine the possible modulation of the activity of cisplatin by flaxseed using different durations of applications. Material and Methods: OSCC cell line cells were cultured and the MTT assay was used to assess cell metabolic activity. Results: The antiproliferative effect of flaxseed oil at 24 and 48 hours as measured by the IC50 was 71.48±4.26 ug/ml and 18.11±1.36 ug/ml respectively. The mean percentage of viable cells at 24 and 48 hours when treated with flaxseed oil was 66.2+/-14.6 and 56.3+/-12.7, p-value <0.001. At 24 hours, the antiproliferative effect of cisplatin alone vs. when combined with flaxseed oil as measured by the IC50 was 9.59 +/- 0.32 ug/ml vs. 12.91+/- 0.94 ug/ml. The mean percentage of viable cells when treated with cisplatin alone vs. flaxseed oil combined with Cisplatin was 52.8+/- 14.4% vs. 55.1+/-15.5%, p-value=0.02. At 48 hours, the antiproliferative effect of cisplatin alone vs. when combined with flaxseed oil as measured by the IC50 was 2.70±0.11 ug/ml vs. 1.55±0.04 ug/ml. The mean percentage of viable cells when treated with cisplatin alone vs. flaxseed oil combined with Cisplatin was 45.4+/- 12.1 vs. 42.1+/-12.5, p-value=0.004. Conclusion: Further studies to explore potential mechanisms of the anticancer effect of flaxseed oil are needed.